Environmental impacts on barley grain composition and longevity - Dufková, Hana; Berka, Miroslav; Psota, Vratislav; Brzobohatý, Břetislav; Černý, Martin (Journal of experimental botany, 2023)
To counter projected reductions in yields of the major crop barley, it is essential to elucidate the mechanisms of its resilience. To assist such efforts, we collected grains from plants grown in fields at 12 testing stations, with suitable temperature and precipitation gradients for identifying environmentally induced changes in their protein and metabolite contents. We then subjected the grains to detailed molecular analysis. The results showed that numerous metabolites and at least a quarter of the grain protein content was modulated by the environment, and provided insights into barley seed production under abiotic stress, including alterations in ribosomal proteins, heatshock protein 70 family proteins, inhibitors, storage proteins, and lipid droplet formation. Potential positive and negative markers of yield were also identified, including the phenolic compound catechin and storage protein levels, respectively. Complementary analyses of barley seedlings and Arabidopsis seeds, respectively, confirmed the role of the identified proteins in abiotic stress responses and highlighted evolutionarily conserved mechanisms. In addition, accelerated ageing experiments revealed that variations in the environment had stronger effects on seed longevity than the genotype. Finally, seeds with the highest longevity differed from the others in gibberellin contents, H2O2 metabolism, and levels of >250 proteins, providing novel targets for improving resilience.
Keywords: semena rostlinná; Longevity; životní prostředí; proteome; drought; barley; Arabidopsis; dlouhověkost; Hordeum; Environment; longevity; peroxid vodíku; Seeds; Hydrogen Peroxide; temperature; gibberellin; metabolome; ječmen (rod); grain protein; seed development; Abiotic stress